Post-mortem human brain analysis of the ventral pallidum in alcohol use disorder - Ameer Elena Rasool; Cormac Peat; Jie Liu; Greg Sutherland; Asheeta A. Prasad (Addiction Neuroscience)
Objective: Alcohol use disorder (AUD) is characterised by cycles of alcohol misuse, abstinence, and relapse. The neurobiology of AUD strongly implicates the role of the ventral pallidum (VP) in a variety of drugs of abuse, including alcohol. Pre-clinical studies have demonstrated critical role of parvalbumin and calretinin neurons in the VP in modulating relapse, mood, and motivation. However, there are a limited studies examining the VP at the cellular level in AUD in humans. Method: Post-mortem human brain tissue of AUD (n = 11), remission (n = 6), and control brains (n = 12) were processed for immunohistochemistry to examine the presence and changes in parvalbumin and calretinin neurons in the VP. Results: Similar to pre-clinical rodent models, parvalbumin and calretinin neurons were present in the VP, although no significant difference was found in their number or morphology across all AUD, remission, and control brains. Conclusion: The presence of parvalbumin and calretinin neurons in the VP was confirmed across all groups. This is particularly important as it supports the translatability of previous animal studies regarding the role of parvalbumin and calretinin neurons in AUD, and thus further implicates the VP in the neurobiology of AUD in humans. As there are no distinctions in the number or morphology of these neurons, their significance likely lies in their activity. The presence of both parvalbumin and calretinin in humans, particularly in both control and AUD cases supports translational capacity from preclinical findings is more feasible.